Closed-loop supply chain network redesigning model post the horizontal merger based on environmental responsibility. (2016) - Yang, Yu-Xiang; Niu, Liang; Huang, Zuqing; Zhou, Gengui
Horizontal merger lead to firms having redundant branches competing in their closed-loop supply chain network at the same market. Furthermore, horizontally merged firms still have some competitors in the market after the merging has occurred. In this paper, an initial closed-loop supply chain network is developed based on operation activities after the horizontal merger. Further, the governing Nash-Cournot equilibrium conditions of competitive firms are analysed. Using the method of variational inequality and equilibrium theory, the optimality conditions for the firms and the corresponding variational inequality formulations are established. Consequently, a multi-criteria network redesign model of the closed-loop supply chain is developed in which the decision makers are faced with multiple criteria, including environmental ones. Finally, numerical examples are solved by using the proposed models to redesign the closed-loop supply chain network after the horizontal merger and analyse the change in equilibrium results of various economic indicators under different parameters.